Talons Cusp in Mandibular Anteriors An Unusual Presentation in A Child Patient (Bangladesh Journal of Child Health, 2012)
Talons cusp is a dental anomaly also known as an eagles talon. It is an extra cusp on an anterior tooth which arises as a result of evagination on the surface of a crown before calcification has occurred. The exact etiology is unknown. The incidence is less than 6%. Commonly involved is maxillary lateral incisors, with some instances of bilateral involvement. The anomaly has been reported to be rare in the mandible. This article reports unusual case of talons cusp, which affecting permanent mandibular central incisors. DOI: http://dx.doi.org/10.3329/bjch.v36i1.13041 Bangladesh J Child Health 2012; Vol 36 (1): 51-52